Textbook of animal diseases - Kumar, Ashok (New Delhi Sonali Publication, 2022)
The present title Animal Diseases" is an Introductory Level text on the biological principles of human diseases which will appeal to medical students and students on degree courses in biomedical science and allied health. The text fuses physiological and biochemical processes underlying the clinical manifestations of disease and there by brings together material that is conventionally dealt with by several books. The clinical relevance is stressed by the inclusion of detailed case studies which highlight the application of basic science to an understanding of